The Influence of Cost Standards, Performance Evaluation, Cost Analysis, and Budget Participation on Employee Managerial Performance at The BPKP Office in Medan City for the 2024 Period - Yesinta Alde Rosari Manalu; Nina Purnasari; Natalia Br Pelawi; Rini Herliani (CV Putra Publisher, 2026)
This study aims to analyze the influence of cost standards, performance evaluation, cost analysis, and budget participation on employee managerial performance at the Medan Financial and Development Supervisory Agency (BPKP) Office. This study uses a quantitative approach with multiple linear regression analysis methods. The population in this study consisted of all BPKP Medan employees, totaling 50 people. The sampling technique used was saturated sampling, where the entire population was taken as the research sample. The data used were primary data obtained through distributing questionnaires to respondents. The results of the study indicate that partially, cost standards do not have a significant effect on managerial performance. Meanwhile, performance evaluation, cost analysis, and budget participation have a positive and significant effect on managerial performance at the Medan BPKP Office. Simultaneously, all independent variables have a significant effect on managerial performance. Thus, it can be concluded that increasing the implementation of performance evaluation, cost analysis, and budget participation optimally can improve managerial performance at the Medan BPKP Office, while cost standards have no significant effect.